2020
DOI: 10.1177/1054773820968036
|View full text |Cite
|
Sign up to set email alerts
|

“Those Plates That Save Me”: Experiences of Italian Patients With Implantable Cardioverter Defibrillator

Abstract: This study aimed to investigate and understand the experiences and feelings lived by people with an ICD. Qualitative study, semi-structured interviews were conducted with a sample of 16 patients, during the annual follow-up. A hermeneutical analysis of the interviews was carried out to identify the themes. Four main themes were classified: “My heart falls asleep,” highlighting a reduced awareness of the pathology and ICD installation; “But what is this thing. . .?” underlining the lack of information and fears… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Among them, 207 (68.77%) were male, 94 (31.23%) were female, 194 (64.45%) were married, 47 (15.61%) were single and others, the marital status of 60 (19.94%) people is unclear, 248 (82.39%) had ICD, 36 (11.96%) had PM, 17(5.65%) had cardiac resynchronization therapy-defibrillator (CRT-D). Of the 18 articles included, 7 were phenomenological studies [ 10 , 12 , 13 , 14 , 18 , 23 , 27 ], 5 were descriptive qualitative studies [ 11 , 16 , 24 , 26 , 28 ], 4 were grounded theory studies [ 15 , 17 , 19 , 29 ], 1 was interpretive interactionism study [ 25 ], and 1 was deductive exploratory study [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among them, 207 (68.77%) were male, 94 (31.23%) were female, 194 (64.45%) were married, 47 (15.61%) were single and others, the marital status of 60 (19.94%) people is unclear, 248 (82.39%) had ICD, 36 (11.96%) had PM, 17(5.65%) had cardiac resynchronization therapy-defibrillator (CRT-D). Of the 18 articles included, 7 were phenomenological studies [ 10 , 12 , 13 , 14 , 18 , 23 , 27 ], 5 were descriptive qualitative studies [ 11 , 16 , 24 , 26 , 28 ], 4 were grounded theory studies [ 15 , 17 , 19 , 29 ], 1 was interpretive interactionism study [ 25 ], and 1 was deductive exploratory study [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…1 and Table 2 (Ref. [10][11][12][13][14][15][16][17][18][19][23][24][25][26][27][28][29][30]), a total of 2117 articles were retrieved from the databases, and 18 were finally included after deduplication and screening [10][11][12][13][14][15][16][17][18][19][23][24][25][26][27][28][29][30]. Publication dates ranged from 2000 to 2022.…”
Section: Summary Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperoside is an active flavonoid glycoside present in numerous medicinal plants such as Epimedium, Hypericum perforatum and Hypericum (10). Previous studies have shown that hyperoside has a wide range of pharmacological effects, including anti-inflammation (11), anti-oxidation (12) and anti-apoptosis (13).…”
Section: Introductionmentioning
confidence: 99%
“…For example, hyperoside plays an anti-inflammatory role in sepsis-related cardiac insufficiency (14), acute lung injury (15) and acute liver injury (16). in addition, hyperoside was able to attenuate the il-1β-induced ecM destruction of chondrocytes (10). However, the role of hyperoside in idd has not been investigated thus far.…”
Section: Introductionmentioning
confidence: 99%